The influence of counseling guidance in minimizing bullying behavior in students of class VII-1 uptd state junior high school 3 BP Mandode subdistrict. BP. Mandoge Asahan Regency - Dorkas Tampubolon (Journal of Education Innovation and Curriculum Development, 2023)
Students who are victims of bullying by their friends at school will potentially feel threatened and have no self-confidence. Schools are obliged to be aware of every incident that occurs in their school environment by involving all students at school and guidance and counseling teachers. The aim of this research was to find out whether class VII-1 experienced bullying incidents. This research uses a qualitative research approach with descriptive methods taken from the perspectives of various students. The respondents of this research were class VII-1 students from SMP Negeri 3 BP. Mandode District. BP. Mandoge Asahan District with a total of 10 students. Based on the results obtained, class VII-1 had many victims of verbal and psychological bullying.